Durability of the multicomponent nitride coatings based on TiN and (Ti,Al)N deposited by PIII&D method - Vasyliev, V.V.; Goltvyanytsya, V.S.; Goltvyanytsya, S.K.; Luchaninov, A.A.; Marinin, V.G.; Reshetnyak, E.N.; Strel'nitskij, V.E.; Tolmachоva, G.N. (Вопросы атомной науки и техники, 2015)
The multicomponent nitride coatings based on TiN and (Ti, Al)N with small additions of Y, Re, Ni, Cr, Si, Mo, Fe synthesized by the PIII&D method from the filtered cathodic-arc plasma. The crystalline nitride phase in all coatings is of the cubic structure of NaCl type. All investigated coatings were characterized with the hardness of 23…36 GPa and Young's modulus of 324…436 GPa. The addition of dopants reduces the average rate of cavitation and abrasive wear of the coatings. The best durability demonstrated coating deposited from the cathode of the Ti₀.₄₉Al₀.₅₀Y₀.₀₀₆Re₀.₀₀₀₅ composition. This coating also demonstrated high thermal stability. Многокомпонентные нитридные покрытия на основе TiN и (Ti, Al)N с малыми добавками Y, Re, Ni, Cr, Si, Mo, Fe синтезированы PIII&D-методом из фильтрованной катодно-дуговой плазмы. Во всех исследованных покрытиях обнаружена кристаллическая нитридная фаза с кубической структурой типа NaCl. Покрытия характеризуются твердостью 23…36 ГПа и модулем Юнга 324…436 ГПа. Добавка примесных элементов приводит к уменьшению средней скорости кавитационного и абразивного износа покрытий. Наилучшую стойкость и термостабильность показало покрытие, осажденное из катода состава Ti₀.₄₉Al₀.₅₀Y₀.₀₀₆Re₀.₀₀₀₅. Багатокомпонентні нітридні покриття на основі TiN й (Ti, Al)N з малими домішками Y, Re, Ni, Cr, Si, Mo, Fe синтезовані PIII&D-методом з фільтрованої катодно-дугової плазми. У всіх досліджених покриттях виявлено кристалічну нітридну фазу з кубічною структурою типу NaCl. Покриття характеризуються твердістью 23…36 ГПа та модулем Юнга 324…436 ГПа. Додавання домішкових елементів призводить до зменшення середньої швидкості кавітаційного та абразивного зносу покриттів. Найліпшу стійкість та термостабільність має покриття, осаджене з катоду складу Ti₀.₄₉Al₀.₅₀Y₀.₀₀₆Re₀.₀₀₀₅.